Recent Progress on Polymers of Intrinsic Microporosity and Thermally Modified Analogue Materials for Membrane‐Based Fluid Separations. Issue 9 (14th September 2021) - Wang, Yingge; Ghanem, Bader S.; Ali, Zain; Hazazi, Khalid; Han, Yu; Pinnau, Ingo
Abstract : Polymers of Intrinsic Microporosity Recent progress on polymers of microporosity and their thermally‐treated analogs for membranebased fluid separations are highlighted by Yingge Wang, Yu Han, Ingo Pinnau, and coworkers in article number 2100049 . Challenges and opportunities are identified for these materials in energy‐intensive separations such as CO2 /CH4, C2 H4 /C2 H6 and C3 H6 /C3 H8 separations, as well as for thin‐film composite membranes containing polymers of intrinsic microporosity (PIM) motifs in liquid applications.